Study of the correlation between the surface roughness and the characteristic of the acoustic signal from laser texturing process - Wan Muhammad Aliff, Wan Mohd Jailani; Mohd Fadhlan, Mohd Yusof; Quazi, Moinuddin Mohammed; Halil, M.A.; Mahadzir, Ishak@Muhammad (Institution of Engineering and Technology, 2022)
Growing attention to the laser texturing technology from various industries lately lead to the collective number of studies related to the process optimization. However, in the application related to the process of turning metallic surface into hydrophobic characteristic, process optimization is not the only factor of the quality assurance of the laser-textured surface. The application of real-time monitoring was found to be significant factor to aid in obtaining the desired quality. This paper present the study of the correlation between the surface roughness of the laser-textured surface and the characteristic of sound signal acquired from the process in order to evaluate the feasibility of this signal to monitor the process by a real-time basis. To achieve the goal of the study, laser texturing process had been done on the 316L stainless steel with the different set of peak power and scanning speed. The sound signal was captured between 20 Hz to 20 kHz during the process. The analysis results show that the sound signal recorded the larger amplitude and root means square (RMS) with the increment of laser peak power, and declining scanning speed. This trend show that the RMS of sound increase as the roughness of the textured surface increase. The overall results trend show that the characteristic of sound signal could give the significant information related to the roughness of the textured surface which were produced from different laser parameters. Thus, with further advancement, acoustic method could possibly be used as the real-time monitoring system for a laser texturing process.